Performance evaluation of bond funds and money market funds in Malaysia - Aminah Shari; Pang, Joo Vee; Choo, Qin Jing; Chin, Dominic Shien Piaw; Lee, Pei Chi; Leong, Wei Zee (Academic Inspired Network, 2023)
This study focuses on the research of bond funds and money market funds in Malaysia due to the lack of research regarding these two funds. It evaluates the performance and differences of bond funds versus money market funds in Malaysia by using Sharpe ratio, Treynor ratio and Jensen’s Alpha as it is widely used by scholars to evaluate the performance of mutual funds. The collection period of our data is from 1st January 2012 until 30th April 2020. Our findings showed that in terms of Sharpe ratio, bond funds perform better than money market funds. Meanwhile for both Treynor ratio and Jensen’s Alpha, money market funds perform better than bond funds. Overall, our findings suggest that money market funds have a better performance as compared to bond funds.